Clinicopathological Features and Treatment outcomes of surgical site Tuberculosis:A Prospective Observational Study (Journal of Medicine, 2026)
Introduction: Post-operative surgical-site infection by tuberculosis is rare condition.The objective of the study was to observe clinicopathological features and treatment outcomes of such patients.Methods: This prospective study conducted on 23 patients with histologically diagnosed surgical site TB. Patients with a history of surgery then non-healing, discharging surgical site for more then one month were included.After tissue diagnosis of TB, anti-TB CAT 1 was given to all patients and observed. Informed written consent from all patients and ethical clearance was taken.Results: Among 23 patients, most were female (87%) and in the 25 to 36 year age group. Most 19(82.4%) patients were from Gynae and Obs and rest 4(17.6%) were from Surgery. 19(82.4%) patients undergone LSCS with Pfennenstiel incision and others from Surgery. 8 (34.8%) presented with wound gap 17(73.9%) cases with wound pain and all had wound discharge pus(73.9%) or serous(26.1%).Three cases had DM(13.04%). Family history of PTB had 2(8.68%) cases.Among all, 15(65.2%) had MT Positivity (>10 mm), two cases were positive for both pus for AFB and gene Xpert, 16(69.56%) cases had Hb